A Randomized Controlled Study: Comparing the Effectiveness of iSCOPE 3 and AirTraq Video Laryngoscope Examinations in Patients Undergoing Tracheal Intubation - Parveen, Sania; Ahmed, Syed Moied; Khan, Mohd Najmul Aqib (Faculty of Medicine-Universitas Airlangga, 2024)
Introduction: Nowadays, indirect laryngoscopy is a commonly used technique for teaching airway control skills. Incorporating small, less expensive, and yet more reliable video cameras into laryngoscopes has given the process of laryngoscopy and intubation, a big leap. The AirTraq has shown promise in several settings, while the iSCOPE 3 video laryngoscope is a newly launched device, and no literature is available to our understanding. Objective: To compare the effectiveness of the iSCOPE 3 video laryngoscope with the AirTraq optical laryngoscope. Methods: It was a randomized controlled study conducted among sixty patients after approval from the Board of Study and ethical clearance, divided into two groups. In Group AT, patients were intubated with AirTraq, and in Group IS, patients were intubated with iSCOPE 3 as per the protocol. The primary outcome metric was the duration of tracheal intubation. Secondary outcomes were measured by the quantity of tries and intubation ease, glottic view or percentage of the glottic opening score (POGO), and Cormack & Lehane grade. Results: In the iSCOPE 3 and AirTraq groups, comparable mean intubation times were observed. (19.50 s vs. 19.16 s). The ease of intubation was significantly better with iSCOPE 3 (p< 0.05), single attempt was needed to intubate 96.7% of patients in the iSCOPE 3 group compared to 70% of patients in the AirTraq group (p< 0.05). POGO score and Cormack & Lehane grade were also significantly better with iSCOPE 3 (p <0.05). Conclusion: Pogo and CL grade were better with iSCOPE 3 than AirTraq, and hence the success rate of intubation, number of attempts, and ease of intubation were significantly better with iSCOPE 3.